2011
DOI: 10.1021/cm2000649
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based Non-Noble-Metal Catalysts for Oxygen Reduction Reaction in Acid

Abstract: Non-noble-metal catalysts based on Fe–N–C moieties have shown promising oxygen reduction reaction (ORR) activity in proton exchange membrane fuel cells (PEMFCs). In this study, we report a facile method to prepare a Fe–N–C catalyst based on modified graphene (Fe–N–rGO) from heat treatment of a mixture of Fe salt, graphitic carbon nitride (g-C3N4), and chemically reduced graphene (rGO). The Fe–N–rGO catalyst was found to have pyridinic N-dominant heterocyclic N (40% atomic concentration among all N components) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
272
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 435 publications
(291 citation statements)
references
References 65 publications
16
272
1
2
Order By: Relevance
“…The efficiency of Li-air batteries, to some extent, is limited by the slow kinetics of the oxygen reduction reaction (ORR) and the OER (22,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). To assess their ORR and OER catalytic activity, our materials were first loaded (with the same mass loading) onto glassy carbon electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of Li-air batteries, to some extent, is limited by the slow kinetics of the oxygen reduction reaction (ORR) and the OER (22,(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). To assess their ORR and OER catalytic activity, our materials were first loaded (with the same mass loading) onto glassy carbon electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…It is clear the N1 and N2 predominate among the nitrogen species, which may be responsible for the ORR active sites [28,46]. The pyridine-N assignment have two edge carbon atoms bond to it, with a lone pair of electrons, often observed on the edge of graphite plane.…”
Section: Surface Analysismentioning
confidence: 99%
“…For instance, FeN 4 G, CoN 4 G, NiN 4 G, and MnN 4 G have been applied for the oxygen reduction reaction (ORR) applications. [23][24][25][26] Later, the possible use of FeN 4 G as a catalyst for NO reduction via the (NO) 2 adsorption mechanism was suggested by the periodic DFT method. 27 Very recently, water dissociation on MN 4 G (M ¼ Mg, Ba, Ti) was theoretically studied by Liu et al 28 They showed that Mg, Ba, Ti are energetically stable on the surface and TiN 4 G displayed promising catalytic properties for H 2 O dissociation.…”
Section: -17mentioning
confidence: 99%